A process o f building 3D models from images - Duy, Bui The; Chau, Ma Thi (VNU Journal of Science: Mathematics - Physics, 2007)
Recently, a number o f new technologies to capture 3D data have been đevelopeđ. The application potential o f 3D models is enormous, such as, in education, entertaúunent, medicine, etc. In this paper, we present our work toward creatìng 3D model o f free form objects from pair of images. We use the basic process o f building 3D models proposed in M u l t i p ỉ e V i e w G e o m e í r y in Compute r Vision by Richard Harlley and Andrew Zisserman which includes three main phases: Preprocessing, Matching, Depth Recovery.